New journalism in documentary script writing - Indra, Syirfan; Yassin, Megat Al Imran; Shekh Alsagoff, Syed Agil; Bidin, Rosmiza (Human Resource Management Academic Research Society, 2023)
The authoring of documentary scripts is frequently overlooked when judging a documentary’s quality. This could be because the documentary script is regarded as merely a tool that has little impact on the final output of the film. Documentaries in Malaysia are considered as sluggish, with a “soft culture” approach to documentary production, despite the fact that the world of documentary production has evolved to a “dramatic entertainment” approach. Researchers propose a literary device-based writing style called as New Journalism as a possible option for documentary writers across the country. In comparison to traditional types of writing, this style combines factual and fictional writing to produce literature that is more creative, new, and alive. It is intended that by using a new type of journalism to write documentary scripts, scriptwriters will modify their approach to producing works, resulting in documentaries that are more skilful, competitive, and relevant to the demands of today’s audience.